ONLINE DISPUTE RESOLUTION ON INTELLECTUAL PROPERTY CASE STUDY PLANTS VARIETY PROTECTION - Sri Sumarlinda; Rina Arum Prastyantia (UNEJ e-Proceeding, 2017)
In Indonesia the protection of plant varieties is regulated in the Law: No. 29 of 2000 onthe Protection of Plant Varieties. This law provides protection to crop varieties provided thatthe discovery of new varieties, Different, Uniform / Uniform, Stable and Have excellence.Disputes in terms of protection of plant varieties. The law is useful to provide protection andanticipation as well as to resolve disputes over plant varieties. In an effort to resolve thedispute, the Court will also be affected by globalization. Many countries, especially developingcountries, must adapt and renew their justice system, because of the urgency of internationalneeds. In the international sphere due to territorial and procedural costs, more and moredispute parties are using alternative mechanisms to resolve their disputes. The purpose ofthis research is to know the possibility of Online Dispute Resolutions on Intellectual PropertyCase study Plants Variety Protection.This research is non doctrinal research. The type of data used in this study is secondarydata. Data collection techniques used are literature and data analysis techniques usinginteractive analysis.Result and conclusions this study that Online Dispute Resolution (ODR) is a disputeresolution that takes advantage of the Internet. ODR is not just an online version ofAlternative Dispute Resolution (ADR), but often called online ADR, eADR, iADR, virtual ADR,cyber mediation, or cyber arbitration, the ODR has many unique aspects both from atechnological and process perspective. ODR is effective to resolve disputes of Plant VarietyProtection due to; The flexible nature of the ODR by utilizing outstanding Internet technologyfeatures, making ADR an appropriate instrument for resolving conflicts quickly andefficiently.